2018
DOI: 10.14419/ijbr.v6i1.9374
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of canine parvoviral enteritis in pet dogs at Dhaka city of Bangladesh

Abstract: Background: Canine parvoviral enteritis is a highly contagious viral disease of dog that can lead to life-threating illness.Objectives: The present study was conducted to determine the prevalence of canine parvoviral enteritis in dogs of Dhaka City Corporation, Bangladesh.Methods: A total of 545 dogs were examined at Dr. Sagir’s Pet Clinics and Research Centre, Dhaka during September 2016 to August 2017. The disease was diagnosed on the basis of clinical history, clinical signs and by CPV rapid Ag kit test.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Ali et al [17] reported higher prevalence (40%) of CPV in Egypt. Also Archana Shukla et al [18] and Roy et al [19], reported higher prevalence of 45.30% and 65.04% respectively in India. These variations observed in the prevalence were difficult to explain due to the different study areas and differences in the methods of sample analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al [17] reported higher prevalence (40%) of CPV in Egypt. Also Archana Shukla et al [18] and Roy et al [19], reported higher prevalence of 45.30% and 65.04% respectively in India. These variations observed in the prevalence were difficult to explain due to the different study areas and differences in the methods of sample analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the proportional incidence of parvovirosis was higher than other viral diseases, which showed a semblance with the findings of Behera et al (2015) where they reported 40.5% of viral diseases was attributed due to parvovirosis in Odisha, India. A previous study showed that most of the stray dogs in the Dhaka city were unvaccinated against parvovirosis (Tenzin et al, 2015) and lack of vaccination was identified as a key determinant of the occurrence of the disease in dogs by Roy et al (2018). These circumstances might attribute to a high burden of parvovirosis in the Dhaka city.…”
Section: Discussionmentioning
confidence: 99%
“…In Table 1, most of the evidence designates (Roy et al, 2018) 2017-2018 Jabalpur (India) 7.24 7.91 6.36 N/A N/A 12.57 4.43 N/A N/A N/A (Khare, 2019) that the proportion of CPV contamination is very eminent in male individuals rather than female; meanwhile, the puppies below one year aged and pure breed dogs are more receptive to the viral infection. Therefore, the study is in line with the previous study reported that young puppies are vulnerable to infection due to the biological half-life of the parvovirus maternal antibody (only around ten days), and this natural resistance emanates from the mother, rendering puppies more prone to infections (Roy et al, 2018). However, proclaimed that CPV has also a devastating effect on pure breeds like Rottweilers, German Shepherd, English Springer Spaniels, and Doberman Pinchers.…”
Section: Epidemiology and Risk Factormentioning
confidence: 99%